ANALISIS HUBUNGAN JENIS DAN FREKUENSI MENGKONSUMSI JAJANAN KARIOGENIK DENGAN KEJADIAN RAMPAN KARIES PADA ANAK USIA 5-6 TAHUN DI KOTA PADANG - Febrian Febrian; Rosfita Rasyid; Ditha Noviantika (Andalas Dental Journal, 2013)
Caries is the main problem of oral health. Caries are frequently found in children are milk bottle caries and caries Rampan. Cariogenic food consumption is a Rampant caries etiology. This study was to determine the relationship of type and frequency to consume cariogenic snacks with the case of caries Rampant in children age 5 -6 years.The research method used is analytic observational study design with a cross sectional study, samples were taken purposive methode with total sampling technique and using the chisquare statistical test. Subjects were pre-school age children from 3 unit Pre-school in Padang.There is a significant relationship between the type of consumption of cariogenic snacks with caries Rampant (p=0,005), There is a significant relationship between frequency of consumption of cariogenic snacks with caries Rampant (p=0,000).It is suggested to parents to control and monitor the type and frequency of consumption of cariogenic snacks in children.